2014
DOI: 10.1007/s12192-013-0463-6
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal heat shock induces premature senescence rather than apoptosis in human mesenchymal stem cells

Abstract: Stem cells in adult organism are responsible for cell turnover and tissue regeneration. The study of stem cell stress response contributes to our knowledge on the mechanisms of damaged tissue repair. Previously, we demonstrated that sublethal heat shock (HS) induced apoptosis in human embryonic stem cells. This study aimed to investigate HS response of human adult stem cells. Human mesenchymal stem cells (MSCs) cultivated in vitro were challenged with sublethal HS. It was found that sublethal HS did not affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 60 publications
8
48
1
Order By: Relevance
“…This resistance to cell death relies on different mechanisms depending on the different DNA-damaging agents/doses used, including an elevated apoptosis threshold 16, an efficient antioxidant ROS-scavenging capacity 13 and a prompt activation of the double strand break repair pathways 13,17. Our results are in accordance with the more recent literature that described SIPS as a further response of hMSCs to ionizing radiation 21,40, oxidative stress 18,41, heat shock 19.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This resistance to cell death relies on different mechanisms depending on the different DNA-damaging agents/doses used, including an elevated apoptosis threshold 16, an efficient antioxidant ROS-scavenging capacity 13 and a prompt activation of the double strand break repair pathways 13,17. Our results are in accordance with the more recent literature that described SIPS as a further response of hMSCs to ionizing radiation 21,40, oxidative stress 18,41, heat shock 19.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, hMSCs showed to be highly resistant to apoptosis induced by different genotoxic insults [11][12][13][14][15][16][17], even though the precise resistance mechanisms are not completely understood. Recently it has been reported that another possible response of hMSCs to injury is stress-induced premature senescence (SIPS) [18][19][20][21][22][23][24]. Even if SIPS represents an important tumour suppressive mechanism that irreversibly prevents damaged cells from undergoing neoplastic transformation, it is clearly a double-edged sword [25].…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous data together with the results described in a latter review, MSCs senescence is accompanied by reduced proliferation rate, decreased differentiation potential as well as impaired migratory ability, the outcomes that we revealed after hMESCs infection supplied by Pb [35,[43][44][45]. Therefore, we speculated that the negative effects of transduction with Pb might be mediated by senescence initiation in a part of hMESCs population.…”
Section: Discussionsupporting
confidence: 66%
“…Summarizing the obtained data, we can make several important conclusions: (1) Transduction with Pb induces senescence in a part of hMESCs population According to the modern data, reduced proliferation and migration rates as well as the decreased differentiation capability of MSCs can testify in favor of senescence progression in the population [43]. Previously, we have convincingly shown that senescence is more preferable reaction of hMESCs in response to damage or stress than apoptosis [44,45]. Based on the data described above, further we analyzed whether senescence induction can be the underlying cause of the observed negative effects of LV infection with Pb.…”
Section: The Impact Of LV Infection On the Main Stem-cell Properties mentioning
confidence: 73%
“…Altogether, identically thawed MSCs retain their immune suppressive effect on T‐cell proliferation if they are separated by a physical barrier suggestive that the heat shock response and cytoskeletal disruption in themselves do not abort their suppressor function, but rather that frozen‐thawed MSCs and granzyme+ T‐cells make poor bedfellows. Thus, we speculate that freeze‐thawing induced alterations in the plasma membrane, intracellular pH, and mitochondrial depolarization likely potentiate MSC's susceptibility to T cell mediated killing and may also promote sensitivity to complement‐mediated lysis .…”
Section: Discussionmentioning
confidence: 96%